ANALISA PRODUKTIVITAS DAN BIAYA PENGGUNAAN STRUKTUR KOMPOSIT DAN KONVENSIONAL PELAT LANTAI PADA PROYEK PEMBANGUNAN TAHAP II RSUD DR. M. SOEWANDHIE SURABAYA - Pinky Febrilla Carienta Putri; I Nyoman Dita Pahang Putra; Anna Rumintang Nauli; Zetta Rasullia Kamandang (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2023)
Construction development projects have the opportunity to experience delays with various kinds of obstacles and productivity is one of the main factors determining the course of a development. The research in this final project is processing unit price analysis. Method Statement Approval (MSA). Material Approval Submission (MAS). Time Schedule. and Shop Drawing to analyze time. productivity. and cost in the implementation of floor slab composite structure work. The results of the analysis of this study show that the design productivity between composite and conventional plates is the same. For the productivity of bondek work realization 42.17 m²/Day. wiremesh work 3070.68 Kg/Day and concrete work 126.63 m³/Day. The productivity of conventional slab formwork work is 414.34 m²/Day. iron work 2896.77 Kg/Day and concrete work 81.02 m³/Day. The cost required for the design of the composite slab is Rp. 3,192,534,719 and the realization of Rp. 3,048,592,476. While the cost for the work of the conventional plate plan is Rp. 950,640,926 and the realization of Rp. 1,057,220,736.